Non-resolving atelectasis after foreign body aspiration in a 17-month-old boy : a case report = Perzistirajuća atelektaza nakon aspiracije stranog tijela u 17-mjesečnog dječaka : prikaz bolesnika - Didović, Diana (Array, 2020)
Foreign body aspiration is an important emergency and cause of morbidity and mortality in children. We present a 17-month-old boy who developed pneumonia and atelectasis a few weeks after unnoticed peanut inhalation. Despite prompt foreign body removal atelectasis persisted for three months. This case highlights the importance of timely diagnosis and treatment of foreign body aspiration.